Scattered Wave Simulation Method and Analysis of Influencing Factors - Houhua TENG; Zhanyi HAN; Shuo ZHAO; Junlin YE; Renwei DING (CT Lilun yu yingyong yanjiu, 2024)
In complex geological conditions, especially in the case of small faults and fractures, it is often impossible to use reflected waves for accurate detection. An alternative method is the use of the scattered waves caused by these small structures for seismic exploration. However, with the conventional description and utilization of scattered waves based on time–distance curves, it is difficult to meet the current needs of high-precision exploration. Therefore, starting from the theoretical description method, this study deduces the time–distance curve equation and the wave equation based on Born approximation for describing the propagation of scattered waves. Then, combined with the respective numerical simulation methods, namely, the fast step method to solve the program function method and the finite difference method to simulate the wave equation, the accuracy and influencing factors of the scattered wave description are analyzed. Finally, the corresponding simulation test is designed, and the numerical model is used to further show that the traditional time–distance curve equation can give the accurate time–distance relationship satisfied by the scattered wave, but it is not accurate when combined with the function equation for imaging. The wave equation based on Born approximation can achieve accurate simulation of scattered waves. The resulting assumptions of scatterers and scattering potential have little effect on the final simulation results. Under the premise of ensuring the stability of forward modeling, the higher the dominant frequency of the wavelet, the more accurate is the description of the scattered wave.